Aesthetics and ecology in the post-modern perspective - Zeidler-Janiszewska, Anna (Polskie Studia Krajobrazowe, 2019)
The analysis sets out from the exhibition entitled Ressource Kunst. Die Elemente Neu Gesehen. The author attempts to outline an area which emerges from the encounter of ecology (as a domain of reflection about the human surroundings) and aesthetics (as a discipline concerned with sensory experience) from the standpoint of post-modernism. The inquiry thus focuses on the moment in which contemporary artistic practices “internalize” ecological issues. Aesthetics becomes a branch of ecology, but at the same time ecology becomes a domain within aesthetics. According to the author, post-modernism has offered advantageous perspectives for pursuing ecological postulations.